A new species of Justicia (Acanthaceae: Acanthoideae) from Atlantic Forest of Bahia, Brazil - Santos, Igor Soares Dos; Silva, Marcos José Da (Phytotaxa, 2026)
Justicia gibbosa, a new species from the Atlantic Forest of southern Bahia state, Brazil, is described, illustrated, mapped, and commented on its state of conservation, geographic distribution, morphological relationships, phenology, and systematic position.